Structural characterisation and ACE-inhibitory activities of polysaccharide from Gastrodia elata Blume. Issue 12 (18th June 2019) - Zhu, Zhen-Yuan; Chen, Chun-Juan; Sun, Hui-Qing; Chen, Li-Jing
Abstract: The structural properties and Angiotensin-I converting enzyme (ACE) inhibition activities of a polysaccharide (PGE) extracted from Gastrodia elata Blume were investigated. PGE was extracted using hot water and purified by Sephadex G-200 followed by ultra-filtration. The structural characterisation of PGE was analysed by FT–IR, NMR spectroscopy, specific rotation determination, periodate oxidation-smith degradation, methylation analysis, GC–MS and Congo red test. The results revealed that PGE was composed by glucose, with an average molecular weight of 1.54 × 10 3  kDa. The structure of PGE was 1→3 and 1→4, 6-branched-glucopyranose that had a linear backbone of (1 → 4)-linked-d -glucopyranose (Glcp). ACE-inhibitory activity results showed that PGE was efficient to inhibit ACE and the IC50 value was 0.66 mg/mL. Abstract :